2022
DOI: 10.1101/2022.02.18.481112
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthetic lethality between toxic amino acids, retrograde target genes and chaperones in Saccharomyces cerevisiae

Abstract: The toxicity of non-proteinogenic amino acids has been known for decades. Numerous reports describe their antimicrobial/anticancer potential. However, these molecules are often toxic to the host as well, therefore a synthetic lethality approach can be beneficial. Here we investigated the potential synthetic lethality between toxic amino acids, the retrograde pathway, and molecular chaperones. In Saccharomyces cerevisiae, mitochondrial retrograde (RTG) pathway activation induces transcription of RTG-target gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…In total, we created nine RTG-target gene double mutants. We previously reported that of the parent single mutants, only idh1Δ and idh2Δ show an arginine biosynthesis defect on glucose (-)arginine and glucose (-)lysine (29). Interestingly, idh1Δ and idh2Δ show a greater growth defect on glucose (-)lysine (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In total, we created nine RTG-target gene double mutants. We previously reported that of the parent single mutants, only idh1Δ and idh2Δ show an arginine biosynthesis defect on glucose (-)arginine and glucose (-)lysine (29). Interestingly, idh1Δ and idh2Δ show a greater growth defect on glucose (-)lysine (Fig.…”
Section: Resultsmentioning
confidence: 99%